Features of Identity in Hani al-Raheb's Narrative I Have Drwan a Line in the Sands - Hassan, Talal (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
In the Arabic novel, the issue of identity stands as one apparent problematicality, providing that the concept of identity is unstable. Many a factor interfere to identify it as a term exactly as the basic facotrs do with this probelmaticality: history, inheritance, economy, religion, mythology, ideology, etc. Accordingly, this piece of reseach commences by defining identity, then refers to the changes it undergoes specially the grand unstabilities sweaping the homeland the effects of which have soon reflected apparent changes and emerging offshoots to the identity that have been absent or potential prior to these severe struggles. Afterwards, it handles numerous narrative characters and analyzes the miscellaneous characteristics of their identities. It concludes with the fact that live personae could change their identities, belongingness or attitudes when encountering material or immaterial pressures. Whereas, the imaginative and fictitious have extremely maintained their original identities. To reiterate, it transpires that time, place and ecology play an influencial role on identities of these artistic characters. However, anyone who is not subject to such changes would keep on constant alienation and complaint. ملامح الهوية في رواية " رسمت خطاً في الرمال لـ "هاني الراهب" بحث يسعى إلى تحديد مفهوم الهوية, ويبيّن ظهور هذه الإشكالية في الرواية العربية , ويفصل أكثر في الشخصيات الروائية التي أبدعها الدكتور هاني الراهب في روايته موضوع الدراسة, موضحاً المكونات الأساس لهذه الهويات, حيث يبرز المكون التاريخي, والاقتصادي, والفكري, والأسطوري, و يستحضر الكاتب شخصيات تاريخية معروفة مثل : عمر بن الخطاب, والحجاج بن يوسف الثقفي, وبلقيس, و شخصيات أخرى وجدها في التراث العربي الشعبي والأسطوري مثل: شهرزاد, وشهريار, والخليفة , وعيسى بن هشام , وأفقزاد. ويقدم كذلك شخصيات معاصرة, مثل الرئيس الأمريكي, والحكام المعاصرين الذين يراهم امتداداً لخلفاء عاشوا منذ أكثر من ألف عام, ويخلص إلى نتيجة مفادها أن الصراعات الحادة و الأزمات الكبرى التي يتعرض لها الوطن تساعد في ظهور هويات فرعية كانت كامنة أو غائبة قبل ذلك, وهذا ما ظهر جلياً في رواية هاني الراهب التي ارتبط زمانها ومكانها باحتلال الكويت , ثمّ بهزيمة العراق والغزو الأمريكي للمنطقة , وما نتج عنه من تغير وتبدل في الوعي سرعان ما أدى إلى تشظي الهوية الوطنية و القومية.